Scientific Paper Writing Training Socio-Cultural Themes for Teachers in MGMP Sociology Semarang City - Rini, Hartati Sulistyo; Akhiroh, Ninuk Sholikhah; Safangatun, Ulfa; Rokhmat, Nur (Universitas Negeri Semarang, 2024)
According to Permenpan No. 26 of 2009 concerning functional positions of teachers and their credit points, teachers are required to produce scientific publications or innovative works as part of self-development. In addition, the benefits of writing scientific papers can also be used to complete credit points for promotion. However, the activity of writing scientific papers, especially those published in journals, is still difficult for teachers. Therefore, this scientific paper writing training is important to do. The methods used in this community service activity are lectures and interactive discussions. The lecture contains a presentation that describes material about writing scientific papers, its urgency, and the format for writing articles in scientific journals. The presentation also provides brief and technical instructions on uploading articles to several journals, such as the Social Science Forum Journal and the Community Journal. The results of this community service activity are related to: 1) problems experienced by teachers in compiling scientific papers, and 2) a SWOT analysis of the implementation of scientific paper writing training for teachers at the MGMP Sociology in Semarang City. The problems experienced by teachers are in identifying ideas or written concepts, Sociology teachers still have difficulty determining which ideas are considered interesting, the format for writing articles is still considered difficult to understand because it varies from one journal to another, and teachers are still less confident in expressing ideas in scientific writing standards. The SWOT analysis conducted is used to prepare a follow-up plan for future community service activities.